Effect of soil properties and aging on the toxicity of copper for Enchytraeus albidus, Enchytraeus luxuriosus, and Folsomia candida - Amorim, Mónica João de Barros
In the present study, the effect of the heavy-metal salt copper chloride (CuCl(2)center dot 2H(2)O) in soils freshly spiked (3 d) and aged (70 +/- 10 d; mean SD) was studied in the test species Enchytraeus albidus, E. luxuriosus, and Folsomia candida. Up to nine soils were used: Besides the Organisation for Economic Co-operation and Development (OECD) artificial soil and the Agricultural Testing and Research Agency (Landwirtschaftliche Untersuchungs- und Forschungsanstalt, Speyer, Germany) 2.2 natural standard soils, the others were selected based on the EURO Soil approach, taking into account the effect of different soil parameters (pH, organic matter, grain size distribution, and carbon to nitrogen ratio). Additionally, the effect of the chloride ions was studied separately. The results revealed the following: First, a soil effect was observed; for example, in F. candida, median effective concentrations (EC50s) varied between 262 mg/kg in a sample from the same site as the original EURO Soil 5 soil and greater than 1,000 mg/kg in OECD soil. Second, an aging effect was observed, mainly in F. candida. For example, toxicity of offspring survival was increased twofold in the OECD soil and approximately eightfold with aging in the EURO Soil 7 soil, whereas the enchytraeid species did not react differently after aging. Third, an effect of chloride ions on reproduction of the animals was found; however, this effect was independent of the aging period. Fourth, species variation was seen in terms of sensitivity (EC50), decreasing in the following order: E. luxuriosus > E. albidus >> F. candida. Differences in toxicity of offspring survival between enchytraeids and F. candida might be explained by the different routes of uptake.